Global burden of urinary tract infections in older women from 1990 to 2021 with projections to 2040: a trend analysis of the Global Burden of Disease Study 2021 - Hu, Yongtao; Ma, Wenming; Tang, Kun; Qi, Qiao; Xu, Wenlong; Hu, Ruijie; Liu, Shuchen; Zhang, Kaixuan; Chen, Jing; Liang, Chaozhao (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundComprehensive estimations regarding the worldwide burden of urinary tract infections (UTIs) in older women aged ≥ 65 years are lacking. This study first explored the trends in the burden of UTIs among older women from 1990 to 2021 with projections to 2040.MethodsThe Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021 analytical tool was adopted to calculate the age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), and age-standardized disability-adjusted life-years (DALYs) rate (ASDR). We applied the Joinpoint regression analysis to examine the overall trends by calculating the average annual percentage change. In addition, the trends were further stratified by age group, sociodemographic index, and geographic region. Predictive analysis was employed to make further estimations of the burden until 2040.ResultsThe global ASIR of UTIs among older women remained stable between 1990 and 2021, while the ASMR and ASDR increased substantially during the same period. Moreover, the prediction analysis showed that although the ASIR in older women was projected to decline, the number of incident cases, deaths, and DALYs was forecasted to continue rising. Regionally, in 2021, South Asia experienced the greatest number of incident cases, deaths, and DALYs, and Tropical Latin America had the highest ASIR, ASMR, and ASDR. Between 1990 and 2021, we found Southern Latin America exhibited the largest regional-level increase in the ASIR, ASMR, and ASDR. At the national level, significant disparities in the burden of UTIs among older women were identified in different countries and territories.ConclusionAlthough the ASIR of UTIs among older women has remained stable over the past three decades, the annual number of incident cases, deaths, and DALYs from UTIs has increased substantially. During the same period, a significant upward trend was found in the UTIs-related ASMR and ASDR. With population growth and aging, the burden of UTIs is expected to keep rising in the coming years. These findings can provide valuable perspectives on the distribution and magnitude relating to the burden of UTIs and promote equity in health outcomes.